PREVALENCE OF ALLERGIC DISEASE SYMPTOMS AMONG SCHOOL CHILDREN (American Journal of Interdisciplinary Research and Development, 2024)
The article examines the prevalence of allergic disease symptoms among schoolchildren living in the Surkhandarya region of the Republic of Uzbekistan.